PENGELOLAAN PEDAGANG KAKI LIMA PASAR RUAH SERUMPUN OLEH UPTD PASAR, KEBERSIHAN DAN PERTAMANAN KECAMATAN TUALANG KABUPATEN SIAK - Permatayanda, Suci; ", Ernawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This thesis describes studies of street vendors (PKL) Market Tuah Serumpun By an operation unit area Market, Cleanliness and Landscaping District of Tualang Siak. Aims to identify and analyze the factors that hinder the management of street vendors are still constrained by the availability of relocation inadequate, and the lack of cooperation with police forces and the limited civil pamung praja.Research management Market Tuah Serumpun By an operation unit area Market, Cleanliness and Landscaping District of Tualang Siak. Indicators it is necessary to manage advanced by GR. Terry (2005), Planning, Organizing , Directing, Controlling. This research method Darmadi ( 2013:6) according to a senior official of this research relates to date collction to provide an overview or affirmation of concept subject. Research on current methods of date collection is done by observation and interviews .The result of research and discussion conducted on the Management of street vendors (PKL) Market Tuah Serumpun By an operation unit area Market, Cleanliness and Landscaping District of Tualang Siak, can be concluded that management can not be implemented to the fullest.Keyword : management,vendors